Infection Prevalence and Antibiotic Resistance Levels in Ureaplasma urealyticum and Mycoplasma hominis in Gynecological Outpatients of a Tertiary Hospital in China from 2015 to 2018 - Wei Zhang; Lijuan Li; Xuelian Zhang; Hongshu Fang; Huajian Chen; Changxian Rong (Canadian Journal of Infectious Diseases and Medical Microbiology)
The aim of this study was to estimate the Ureaplasma urealyticum and Mycoplasma hominis infection prevalence and antibiotic resistance levels in gynecological outpatients. Clinical characteristics and laboratory data of gynecological outpatients of the Fourth People’s Hospital of Chongqing from 2015 to 2018 were retrospectively analyzed. Antibiotic resistance levels in U. urealyticum and M. hominis were defined by a commercial Mycoplasma kit for antibiotic susceptibility testing. Univariate analysis and multivariate logistic regression analysis were performed to evaluate risk factors associated with Mycoplasma isolation. Comparisons of yearly distributions and resistance rates were assessed by chi-square tests. Fifty-six percent of gynecological outpatients were positive for U. urealyticum, and 11.02% were positive for M. hominis. In the univariate analysis, women aged 30–39 years or with a history of pregnancy or gynecological diseases had an increased risk for Mycoplasma isolation, while women who were postmenopausal or had an education level of undergraduate degree or above had a decreased risk of Mycoplasma isolation. In the multivariate logistic regression model, an independent risk factor for Mycoplasma isolation was a history of gynecological diseases, while a bachelor’s degree, master’s degree, or above were protective factors against Mycoplasma isolation. There were distinctly gradual increases in the positivity rates of U. urealyticum and M. hominis from 2015 to 2018 and an overall increasing trend of resistance to ten antibiotics among U. urealyticum and M. hominis. The top three antibiotics associated with resistance were ofloxacin, sparfloxacin, and levofloxacin. Doxycycline, josamycin, and minocycline were preferred because they had the lowest levels of resistance. Increases in the prevalence of infection and antibiotic resistance in U. urealyticum and M. hominis were observed from 2015 to 2018, clearly confirming the necessity to monitor the standardized administration of antibiotics.